Association of circulating minerals and vitamins with pregnancy complications: a Mendelian randomization study - Xie, Yuan; Zhang, Jie; Ni, Shuang; Li, Ji (Frontiers in Nutrition, 2024)
Background: Though considerable studies suggesting connections between micronutrients and pregnancy complications, current evidence remains inconsistent and lacks causative confirmation.Our study aimed to explore the causal links between them with a two-sample Mendelian randomization (MR) analysis.Methods: Genome-wide association studies (GWAS) data for circulating micronutrients were sourced from GWAS Catalog consortium and PubMed, while data for pregnancy outcomes, including gestational diabetes mellitus (GDM), gestational hypertension (GH), spontaneous abortion (SA), preterm birth (PTB), and stillbirth (SB), were retrieved from the UK Biobank and FinnGen consortia. Causal effects were appraised using inverse variance weighted (IVW), weighted median (WM), and MR-Egger, followed by sensitivity analyses and meta-analysis for validation.Results: Genetically predicted higher vitamin E (OR = 0.993, 95% CI 0.987-0.998; P = 0.005) levels were inversely associated with SA risk. Consistent results were obtained in meta-analysis (OR = 0.99, 95% CI 0.99-1.00; P = 0.005). Besides, a potential positive causality between genetic predisposition to vitamin B12 and SB was identified in both IVW (OR = 0.974, 95% CI 0.953-0.996; P = 0.018) and WM analysis (OR = 0.965, 95% CI 0.939-0.993; P = 0.013). However, no causal relationships were observed between other analyzed circulating micronutrients and pregnancy complications.This study offers compelling evidence of causal associations between circulating levels of vitamins E, B12 and the risk of SA and SB, respectively. These findings are pivotal for pregnancy complications screening and prevention, potentially guiding clinical practice and public health policies toward targeted nutritional interventions.